Examining the factors that influence an organization's intention to adopt a lean integrated management system in Malaysia food industry - Mohd Sam, Mohd Fazli; Abu Bakar, Kamarudin; Ali, Norazida; Hashim, Nik Mohd Zarifie; Mohd Kasim, Noor Shahida; Sari, Nadia Nila (Penerbit Universiti Malaysia Perlis, 2025)
In today’s era, lean management is progressively important and has shown its potential application in the food industry. Thus, a lean integrated management system (LIMS) is the essential advanced technology that is well-equipped with a management system and lean thinking’s tools to improve the performance of management and technical work. Nevertheless, the problem arises in which the LIMS adoption had a high failure rate in the food industry in Malaysia due to a lack of consideration of both internal and external factors when employing lean management for improving the organizational innovation performance. This explanatory research aims to analyze the determinants involved in influencing the organization’s intention to adopt LIMS in the food industry and how it subsequently impacts the organizational performance. Hence, the Technology Adoption Model (TAM) as a proposed framework and hypotheses was formulated to study the causal relationships among the independent variable as the determinants, including technical lean tools and practices factors, organizational factors, individual factors, managerial factors, and external factors; the organization’s intention to adopt LIMS as the mediating variable; and the dependent variable, which is organizational innovation performance. A quantitative research method with a survey questionnaire was utilized to collect the data from a total of 550 respondents, including the organization’s staff in Malaysia’s food industry. Furthermore, Pearson’s Correlation Coefficient and regression analysis were mainly used to analyze the quantitative data through the software IBMSPSS Statistics25. The analytical results showed that all the relationships between the independent variables and the mediator are significantly positive, while external factors possess the most significant positive relationship with the organization’s intention to adopt LIMS, and ultimately the organization’s intention to adopt LIMS has a significant positive contribution to organizational innovation performance. It concluded that the research benefits the organization in the food industry and the researcher with valuable insights for future study and decision-making in lean adoption.